Evaluating gun policy : effects on crime and violence - Ludwig, Jens; Cook, Philip J., 1946- (Washington, D.C. : Brookings Institution Press, 2003)
Annotation Policymakers have tried to combat gun-related violence and crime in various ways: including sentence enhancements, restricting access, and banning certain models and designs. Yet far too little is currently known about the efficacy of these policies. This book sheds light on what works by presenting rigorous empirical evaluations of a variety of current policies.
Pragmatic gun policy / Philip J. Cook and Jens Ludwig -- Guns and suicide / Mark Duggan -- Guns and burglary / Philip J. Cook and Jens Ludwig -- Australia : a massive buyback of low-risk guns / Peter Reuter and Jenny Mouzos -- Disarming batterers : the impact of domestic violence firearm laws / Elizabeth Richardson Vigdor and James A. Mercy -- Policing crime guns / Jacqueline Cohen and Jens Ludwig -- Prison sentence enhancements : the case of Project Exile / Steven Rafael and Jens Ludwig -- Impact of concealed-carry laws / John J. Donohue -- State and federal gun laws : trends for 1970-99 / Jon S. Vernick and Lisa M. Hepburn -- Data on violent injury / Deborah Azrael [and others] -- Continuity and change in the American gun debate / Franklin E. Zimring.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Gun control -- United States; Violent crimes -- United States; Armes à feu -- Contrôle -- États-Unis.; Crimes violents -- États-Unis.; TRUE CRIME -- General; POLITICAL SCIENCE -- Civil Rights; Gun control; Violent crimes; United States